(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The article is devoted to the study of pedagogical aspects of canoe polo development as a sports discipline and problems of professional training of coach-educators in Ukraine. Canoe polo is characterized as a team water sport that combines kayaking with ball handling technique and tactical play, requiring simultaneous high-level paddling preparation, technical mastery and tactical thinking. The pedagogical foundations of long-term training of canoe polo players are analyzed through the system of sequential stages: initial training aimed at forming interest and basic skills, basic training focused on stable technical skills development, specialized training for advanced technical-tactical improvement and referee-instructor preparation, and training for higher sports mastery oriented towards achieving highest international results. The types of sports training are characterized: physical preparation including general, auxiliary and special training; technical preparation focused on paddling technique and ball handling skills; tactical preparation developing individual, group and team actions; psychological preparation forming volitional qualities and team cohesion. The pedagogical features of teaching paddling technique and ball handling, organization of tactical training and psychological support are determined. Typical training session plans demonstrating pedagogical principles are presented. The problems of professional training of coach-educators in canoe polo are analyzed, including the absence of specialized educational programs in higher education institutions, insufficient methodological support, and limited opportunities for popularization of the sport among sports and scientific community. The role of referee and instructor training as an important component of professional development of coaches is considered. The prospects for developing professional training system are determined: development of specialized educational programs, creation of advanced training system, expansion of methodological base through development of teaching materials and video content, popularization of canoe polo through scientific publications and conferences, involvement of new specialists in coaching process, mass dissemination of the sport among Ukrainian population. The necessity of expanding methodological base for teaching and popularization of canoe polo among sports and scientific community is substantiated.